2018
DOI: 10.1007/s10103-018-2525-6
|View full text |Cite
|
Sign up to set email alerts
|

Less is more: similar efficacy in three sessions and seven sessions of pulsed dye laser treatment in infantile port-wine stain patients

Abstract: Port-wine stains (PWS) affect 0.3 to 0.5% of newborns and pulsed dye laser (PDL) remains the treatment of choice. However, no reliable study regarding the benefits of more frequent has been conducted. We designed the present study to evaluate whether more frequent PDL treatments in infantile patients would achieve further lightening of erythema. We prospectively investigated 20 infants with PWS. Two adjacent sites were both treated for a 12-week duration and randomly allocated to be treated for seven sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…of studies was randomized (i.e., randomization of treatments to different patients or to different sites within one patient and/or PWS) [11,31,36,39,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]61,62,81,92,103]. Of the uncontrolled (noncomparative) studies (N = 42/75 [63][64][65][66][67][68][69][71][72][73][74][75][76][77][78][79][80][82][83][84][85][86][87]…”
Section: Plos Onementioning
confidence: 99%
“…of studies was randomized (i.e., randomization of treatments to different patients or to different sites within one patient and/or PWS) [11,31,36,39,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]61,62,81,92,103]. Of the uncontrolled (noncomparative) studies (N = 42/75 [63][64][65][66][67][68][69][71][72][73][74][75][76][77][78][79][80][82][83][84][85][86][87]…”
Section: Plos Onementioning
confidence: 99%
“…In the first analysis, the data were unclustered to reflect the clinical reality in its broadest sense (Fig. a) . In terms of interventions, a rapid switch from the 577‐nm PDL to longer‐wavelength (585 and 595 nm) PDLs is noted.…”
Section: Resultsmentioning
confidence: 99%
“…tive study of East Asian infants found that frequent PDL treatments (2-week intervals) did not necessarily increase efficacy and resulted in more side effects such as eczematous dermatitis 27. This may be attributed to the increased melanin in East Asian skin.…”
mentioning
confidence: 98%